Human casualties in earthquakes progress in modelling and mitigation - Spence, R. J. S. (Robin J. S.).; So, Emily; Scawthorn, Charles; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
Assessment of human casualties in earthquakes has become a topic of vital importance for national and urban authorities responsible for emergency provision, for the development of mitigation strategies and for the development of adequate insurance schemes. In the last few years important work has been carried out on a number of recent events (including earthquakes in Kocaeli, Turkey 1999, Niigata Japan, 2004, Sichuan, China 2008 and L'Aquila,Italy 2009). These events have created new and detailed casualty data, which has not until now been properly assembled and evaluated. This book draws the new evidence from recent events together with existing knowledge. It summarises current trends in the understanding of the factors influencing the numbers and types of casualties in earthquakes; it offers methods to incorporate this understanding into the estimation of losses in future events in different parts of the world; it discusses ways in which pre-event mitigation activity and post-event emergency management can reduce the toll of casualties in future events; and it identifies future research needs. Audience: This book will be of interest to scientists and professionals in engineering, geography, emergency management, epidemiology and the insurance industry.
Preface -- 1. Introduction -- 2. Earthquakes: an Epidemiological Perspective on Patterns and Trends -- 3. Earthquakes Casualty Research and Public Education -- 4. Disaster Casualties ? Accounting for Economic Impacts and Diurnal Variation -- 5. A Global Earthquake Building Damage and Casualty Database -- 6. Earthquake Casualty Models within the USGS Prompt Assessment of Global Earthquakes for Response (PAGER) System -- 7. Loss Estimation Module in the Second Generation Software QLARM -- 8. Earthquake Casualties Estimation In Emergency Mode -- 9. Estimating Casualties for the Southern California Shakeout -- 10. Casualty Estimation due to Earthquakes: Injury Structure and Dynamics -- 11. Seismic Vulnerability and Collapse Probability Assessment of Buildings in Greece -- 12. Seismic Casualty Evaluation- the Italian Model an application to the L?Aquila 2009 Event -- 13. Mortality and Morbidity Risk in the L?Aquila, Italy Earthquake of 6 April 2009 and Lessons to be Learned -- 14. Major Factors controlling Earthquake Casualties as revealed via a Diversified Questionnaire Survey in Ojiya City for the Mid-Niigata Earthquake -- 15. Advances in Casualty Modelling facilitated by the USGS Prompt Assessment of Global Earthquakes for Response (PAGER) System -- 16. Challenges in Collating Earthquake Casualty Field Data -- 17. Estimating Human Losses Earthquake Models: A Discussion -- 18. Trends in the Casualty Ratio of Injured to Fatalities in Earthquakes -- 19. Study of Damage to the Human Body caused by Earthquakes: Development of a Mannequin for the Thoracic Compression experiments and Cyber Dummy using Finite Element Method -- 20. A Different View on Human Vulnerability to Earthquakes: lessons from risk perception studies -- Index.
Electronic reproduction.
Keywords: Earthquake hazard analysis; Mass casualties; Electronic books